Analisis Perbandingan Kinerja Keuangan PT Bank Syariah Indonesia, Tbk dan PT Bank Muamalat Indonesia pada Tahun 2020-2023 - Dwi Lailatul Hidayah; Sania Rahmawati; Uswatun Chasanah (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of financial statements is to provide data that refers to the financial function, achievements (business results) of an organization and adjustments to the financial function of an institution that are beneficial to customers in making financial decisions. The research method used is a quantitative method. This research method uses literature research, which is a technique of collecting records of the use of notes and analyzing theories from various literature related to research. The improvement of Islamic banking through laws, guidelines for Indonesian financial institutions and the fatwa of the Indonesian Ulema Council with the existence of the Sharia-MUI Council is a concrete and tangible step as an effort to realize the dream of mankind for Islamic banking services and products in Indonesia in 2017. in accordance with modern trends. The decline in capital in Muamalat financial institutions shows that this financial group is starting to experience difficulties. Muamalat economic institutions need a capital boom to increase their capital ratio. With this additional capital, it will be able to help capital at Bank Muamalat Indonesia.